Prediction as memory retrieval: timing and mechanisms. Issue 5 (27th May 2016) - Chow, Wing-Yee; Momma, Shota; Smith, Cybelle; Lau, Ellen; Phillips, Colin
ABSTRACT: In our target article [Chow, W., Smith, C., Lau, E., & Phillips, C. (2015), A "bag-of-arguments" mechanism for initial verb predictions, we investigated the predictions that comprehenders initially make about an upcoming verb as they read and provided evidence that they are sensitive to the arguments' lexical meaning but not their structural roles. Here we synthesise findings from our work with other studies that show that verb predictions are sensitive to the arguments' roles if more time is available for prediction. We content that prediction involves computations that may require differing amounts of time. Further, we argue that prediction can be usefully framed as a memory retrieval problem, linking prediction to independently well-understood memory mechanisms in language processing. We suggest that the delayed impact of argument roles on verb predictions may reflect a mismatch between the format of linguistic cues and target event memories. We clarify points of agreement and disagreement with the commentaries, and explain why memory access mechanisms can account for the time course of prediction.